2022
DOI: 10.1016/j.imr.2022.100832
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of East Asian traditional medicine for treatment of idiopathic short stature in children: Systematic review and network meta-analysis

Abstract: Background Idiopathic short stature (ISS) is a common problem in children and causes many economic and social burdens. In Asian countries, East Asian traditional medicine (EATM) therapies are widely used for children with ISS. In this study, we compared and ranked various EATM therapies for the treatment of pediatric ISS using network meta-analysis. Methods Randomized controlled trials that evaluated various EATMs for pediatric ISS were found through searching 14 electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…We have also previously reported a network meta-analysis [ 13 ] and an observational case series [ 14 ] of integrative KM treatment for ISS. The findings suggested that EATM plus GH might have a synergistic effect in comparison with EATM or GH alone [ 13 ]. In addition, the changes in growth indicators in children with ISS before and after KM treatment showed the potential of KM for the management of ISS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also previously reported a network meta-analysis [ 13 ] and an observational case series [ 14 ] of integrative KM treatment for ISS. The findings suggested that EATM plus GH might have a synergistic effect in comparison with EATM or GH alone [ 13 ]. In addition, the changes in growth indicators in children with ISS before and after KM treatment showed the potential of KM for the management of ISS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we sought the opinions of KMDs regarding their use of these Evidence-Based Complementary and Alternative Medicine treatments. We have also previously reported a network meta-analysis [13] and an observational case series [14] of integrative KM treatment for ISS. e findings suggested that EATM plus GH might have a synergistic effect in comparison with EATM or GH alone [13].…”
Section: Discussionmentioning
confidence: 99%
“…Due to various concerns, such as potential side effects and the fear of frequent injections among children and adolescents, complementary and alternative medical treatments are often sought to increase height growth [15]. Herbal medicine (HM) has been used to treat various diseases and is currently one of the most popular complementary and alternative medicines [16]. HM has been used for thousands of years in East Asia to treat growth disorders and SS.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews on the treatment of SS primarily focused on the effects of GH [10,[19][20][21], and currently, investigations on the effects of HM are also being conducted [16,22]. Several studies have been performed to determine the effects of combination therapy with HM and GH (CHG) for treating SS.…”
Section: Introductionmentioning
confidence: 99%
“…However, complementary and alternative medicine (CAM) treatment is often considered despite the following concerns: reluctance to start artificial hormone therapy at an early age, fear of potential side effects, discomfort of getting an injection every four weeks, and poorer outcomes than expected with regards to the improvement of final adult height [11]. Traditional Korean medicine (TKM) has been used for the treatment of various diseases and is currently one of the most popular CAM [12] treatments. ICPP, which accounts for the highest percentage of PP and is free from other identifiable diseases, can benefit from TKM [11].…”
Section: Introductionmentioning
confidence: 99%